Curli Biogenesis and Function - Barnhart, Michelle M. (2006)
Curli are the major proteinaceous component of a complex extra-cellular matrix produced by many Enterobacteriaceae. Curli were first discovered in the late 1980s on Escherichia coli strains that caused bovine mastitis, and have since been implicated in many physiological and pathogenic processes of E. coli and Salmonella spp. Curli fibers are involved in adhesion to surfaces, cell aggregation, and biofilm formation. Curli also mediate host cell adhesion and invasion, and they are potent inducers of the host inflammatory response. The structure and biogenesis of curli are unique among bacterial fibers that have been described to date. Structurally and biochemically, curli belong to a growing class of fibers known as amyloids. Amyloid fiber formation is responsible for several human diseases including Alzheimer's, Huntington's, and prion diseases, although the process of in vivo amyloid formation is not well understood. Curli provide a unique system to study macromolecular assembly in bacteria and in vivo amyloid fiber formation. Here, we review curli biogenesis, regulation, role in biofilm formation, and role in pathogenesis.